Childhood adversity, pubertal timing and self-harm: a longitudinal cohort study. Issue 16 (8th December 2022) - Russell, Abigail Emma; Joinson, Carol; Roberts, Elystan; Heron, Jon; Ford, Tamsin; Gunnell, David; Moran, Paul; Relton, Caroline; Suderman, Matthew; Mars, Becky
Abstract: Background: The occurrence of early childhood adversity is strongly linked to later self-harm, but there is poor understanding of how this distal risk factor might influence later behaviours. One possible mechanism is through an earlier onset of puberty in children exposed to adversity, since early puberty is associated with an increased risk of adolescent self-harm. We investigated whether early pubertal timing mediates the association between childhood adversity and later self-harm. Methods: Participants were 6698 young people from a UK population-based birth cohort (ALSPAC). We measured exposure to nine types of adversity from 0 to 9 years old, and self-harm when participants were aged 16 and 21 years. Pubertal timing measures were age at peak height velocity (aPHV – males and females) and age at menarche (AAM). We used generalised structural equation modelling for analyses. Results: For every additional type of adversity; participants had an average 12–14% increased risk of self-harm by 16. Relative risk (RR) estimates were stronger for direct effects when outcomes were self-harm with suicidal intent. There was no evidence that earlier pubertal timing mediated the association between adversity and self-harm [indirect effect RR 1.00, 95% confidence interval (CI) 1.00–1.00 for aPHV and RR 1.00, 95% CI 1.00–1.01 for AAM]. Conclusions: A cumulative measure of exposure to multiple types of adversity does not confer an increased risk of self-harm via early pubertal timing, however both childhood adversity and early puberty are risk factors for later self-harm. Research identifying mechanisms underlying the link between childhood adversity and later self-harm is needed to inform interventions.